Kinerja Komisi Pemilihan Umum Dalam penyelenggaraan Pemilihan Kepala Daerah Kabupaten Halmahera Barat - DIMES, YARNES; PANGKEY, MASJE SILIJA; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2018)
AbstractThe General Election Commission's performance in organizing regional elections for West HalmaheraRegency. This study uses qualitative methods (observation, in-depth interviews (Indepeth Interviw),Documentation). The informants of this research were 9 people including, the Chairperson of the WestHalmahera KPU, the Elected Regent of West Halmahera Regency, the Chairperson of the DPC democrat,the head of the Supervisory Committee of West Halmahera Regency, the Subdistrict SupervisoryCommittee, and several community members. The collection techniques used were interviews, while thedata analysis was carried out with qualitative analysis techniques based on the results of this study drawnconclusions: KPUD performance is a policy process in carrying out the duties and responsibilities toproduce good governance in West Halmahera regency.Keywords: Changing Service and Performance Effectiveness.